Global Governance and Security Concerns: A new scenario with respect to India - Jahan, Dr. Almaz (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Covid-19 has put human civilization at a crossroads and is a global threat more precisely a threat without border that cannot be solved by a nation alone rather it demands a global response to ensure global security. Many countries around the world have begun to vaccinate after COVID-19 vaccines became available in December 2020; aiming to save lives of their respective populations as well as ensuring global security. Presently Covid-19 is shaping the contours of global securities which is moving towards a new form of asymmetric security threats and urges for fresh reflections on the issues of global securities. Global security includes military and diplomatic measures that nations and international organizations take to ensure mutual safety and security and assesses the sources of potential regional conflict; and emerging threats to the global security environment and studies, How a range of different security agents interact, cooperate and compete, to produce new institutions, practices and forms of security governance and global studies. In post -cold war era some Neo –Realist, Pluralist and Social Constructivist in I.R. shifted not only the focus from military to non- military nature of global security threats but also security of State to Human Security and brought appraisal of Realist paradigm of I.R. which focused only on Military Security & Inter State Relations. To make global security more meaningful, there is a need to review the current scope and operation of global security and to identifying new threats with a renewed focus on non-military nature of global security threats. Hence, this chapter aims at understanding the current mechanism of global governance and to analyze the effective safeguards to deal with non-traditional security threats such as pandemics as well as analysis of multilateral mechanisms that facilitate the kind of cooperation that will be needed to mitigate the worst impacts of future global crises. Keywords: Military Security, global crisis, pandemic,